2021
DOI: 10.1186/s12905-020-01163-7
|View full text |Cite
|
Sign up to set email alerts
|

Client perceptions of the BreastScreen Australia remote radiology assessment model

Abstract: Background Telehealth and teleradiology are increasingly used around the world to facilitate health care provision when the health care provider and clients are separated by distance. The BreastScreen Australia Remote Radiology Assessment Model (RRAM) is an initiative developed to address the challenges of inadequate access to a local radiological workforce in regional Australia. With the growth in telehealth innovations more broadly, the RRAM represents a departure from the traditional onsite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Our results indicated that when there were well-designed clinical trials in progress 26 , 28 , 31 or patients with common problems, 27 it was easier to conduct observational analytical studies and listen to the members of the population under study. Most of the authors of the retrieved studies had not done previous work on telehealth, with the exceptions of Smith 28 and Goodman-Casanova.…”
Section: Discussionmentioning
confidence: 82%
See 4 more Smart Citations
“…Our results indicated that when there were well-designed clinical trials in progress 26 , 28 , 31 or patients with common problems, 27 it was easier to conduct observational analytical studies and listen to the members of the population under study. Most of the authors of the retrieved studies had not done previous work on telehealth, with the exceptions of Smith 28 and Goodman-Casanova.…”
Section: Discussionmentioning
confidence: 82%
“…Our results indicated that when there were well-designed clinical trials in progress 26 , 28 , 31 or patients with common problems, 27 it was easier to conduct observational analytical studies and listen to the members of the population under study. Most of the authors of the retrieved studies had not done previous work on telehealth, with the exceptions of Smith 28 and Goodman-Casanova. 31 Ferraris colleagues deepened their knowledge about offering telemedicine care in neurosurgery to poor and vulnerable populations in the Philippines by conducting comparative studies between countries and evaluating the use of new digital technology to plan treatment before surgery.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations